Treatment of pregnancy associated metastatic hormone and Her-2 receptor positive inflammatory breast cancer: A real challenge. (2016) - Tran, Phu N.; Mehta, Rita S.
Abstract: Gestational breast cancer is uncommon but poses dilemmas for patients and oncologists. Pregnancy is not a reason to delay treatment but oncologists should be vigilant for potential treatment-related complications to both the fetus and mother. Herein, we report a 29 year old female with metastatic hormone and Her-2 receptor positive inflammatory breast cancer who was found to have trastuzumab induced oligohydramnios in the second trimester. She also developed an asymptomatic decrease in her left ventricular ejection fraction. Discontinuation of trastuzumab led to resolution of oligohydramnios and improvement in her ventricular function. Finally, patient also had durable complete response of her inflammatory breast cancer to sequential doxorubicin, cyclophosphamide and docetaxel followed by trastuzumab, pertuzumab, goserelin and exemestane. We provide in-depth literature review in regards to trastuzumab induced oligohydramnios, trastuzumab associated cardiomyopathy and successful management of IBC during pregnancy.